Aspectos clínicos, epidemiológicos e imunológicos da associação entre periodontite e doenças cardiovasculares, respiratórias e Diabetes Mellitus em indivíduos internados em Unidade de Terapia Intensiva - Barbara Nascimento de Albuquerque (2016)
Periodontitis is an inflammatory disturbance off the periodontal tissues, with progressive loss of the insertion and bone tissue, resulting from the infection and interaction between specific bacterial species and immune-inflammatory response components from the host in susceptible individuals. Periodontal infections are likely a risk factor to several chronic systemic diseases. Hospitalization changes a given individual`s routine, leading to stress and anxiety due to the imminence of pain and discomfort, beyond that, there is the systemic vulnerability and frequent disregard to oral hygiene. This cross-sectional, observational study has evaluated the periodontal condition in clinical, epidemiological and immunological aspects of hospitalized inpatients in the Intensive Care Unit (ICU) of the Hospital São Francisco de Assis Concordia Unit, in Belo Horizonte, Minas Gerais, Brazil. Therefore, this study`s objectives are: (1) to determine the prevalence on periodontitis; (2) identify risk variables associated with the presence of periodontitis; (3) look into the association between presence, severity and extension of the periodontitis and occurrence of cardiovascular diseases (DCV), respiratory diseases (DR) and diabetes mellitus (DM); (4) ascertain the levels of the IL-1, IL-6 and MMP-2 inflammatory markers in those individuals. The final sample had 183 individuals, from both genders, ages between 30 and 82 years old, with average number of teeth of 16.2 ( 6.9), submitted to thorough periodontal evaluation and sampling from the gingival sulcular fluid to immunological analysis through Periotron® and quantification trough ELISA afterwards. As a result, 48.1% of the studied population were found with periodontitis, from those, there was a slight variation between the moderate chronic (51.1%) and advanced (48.9%) forms, but most individuals presented localized periodontitis. The prevalence of DCV, DM and DR were respectively: 68.1%, 30.9% and 10.4%. Association was found between the occurrence of periodontitis and DCV in logistic regression (p=0.024) (OR 2.2; CI=1.11-4.42). DCV individuals presented higher percentage of bleeding on probing sites (SS) (p=0.043) and depth of probing (PS) 4mm (p=0.020). On PS 6mm both DCV (p=0.017) and DR (p=0.023) individuals presented higher percentage of sites in that condition. Beyond that, variables alcoholism (p=0.028) and age range 30 39 years old (p=0.032) were considered risk variables for the occurrence of periodontitis. On the immunological analysis, individuals with periodontitis showed higher levels of IL-1 (p<0.001) and MMP-2 (p=0.025), those with DCV presented higher levels of IL-1 (p=0.029) and those with DM a higher IL-6 (p=0.002). In conclusion, this study reported a high prevalence of periodontitis amongst individuals in the ICU and a positive association between periodontitis and DCV, besides higher levels of IL-1 and MMP-2. Additionally, it has been reported higher levels of IL-1 associated with DCV and higher levels of IL-6 with DM. Thereby, this study recommends specific oral care must be given by trained professionals, preferably dentists, with well stablished protocols so that there is no worsening of the buccal conditions through the hospitalization, in a way that this could contribute to reduce infectious complications on the clinical evolution of the patient, therefore compromising the quality of the service.